Literature Review: Factors Affecting Marketing Strategy, Market Size, Technology, and End Users on Market Segmentation and Competitive Space - Febriyani Putri Antika (The Eastasouth Management and Business, 2023)
The relatively new information technology has amazingly been the trigger for the growth of so many markets for goods and service offerings to become global in the truest sense. Market segmentation is the process of dividing the market into groups of potential customers who have similar needs and/or personalities and have the same reaction to spending their money. The marketing strategy consists of specific strategies related to the market, the target marketing mix, and the level of marketing expenditure. A company's marketing strategy must be able to change in a competitive environment. The purpose of writing this “Literature Review” is to determine the effect or relationship between exogenous variables (marketing strategy, market size, technology, and end users) on endogenous variables (market segmentation and competitive space).